Effects of the level of dietary fat intake and endurance exercise on plasma cytokines in runners - Venkatraman, J. T.; Pendergast, D. (Medicine & Science in Sports & Exercise, 1998)
PURPOSE:Chronic exercise and high fat diets have been associated with immune suppression. We have reported the effects of level of dietary fat and exercise on lymphocyte subsets, proliferative response, and in vitro production of cytokines by peripheral blood mononuclear cells of runners. The present study was planned to further investigate whether the mechanisms of action of dietary fats is through their modulation of plasma cytokines in runners. METHODS: This study compared plasma cytokines at rest and after endurance exercise at 80% of V02max in female (N = 8-10) and male (N = 8-10) runners after eating diets comprised of 17% (LF), 32% (MF), and 41% (HF) fats (4 wk each). RESULTS: The level of interleukin-1 beta (IL-1 beta) was independent of gender, exercise, and level of dietary fat. tumor necrosis factor (TNF-alpha) level was higher in the plasma of men compared with that in women runners, and the level of these two cytokines increased with increasing level of dietary fat. Plasma interleukin-2 (IL-2) level (a cytokine involved in enhancing T cell functions for host defense) was significantly higher in men compared with that in women runners and decreased in men with increase dietary fat. Plasma interleukin-6(IL-6) level was significantly lower after the endurance run, and IL-6 levels decreased with increase in dietary fat. CONCLUSIONS: Data from the present study suggest that dietary fat has differential effects on plasma cytokine levels in runners. Increasing the level of dietary fat significantly increased endurance run time and had no adverse effects on the level of plasma IL-2 and pro-inflammatory cytokines (IL-1 beta, IL-6 and TNF-alpha in runners.